Kepuasan Pengguna Layanan Pencairan Dana ABPN Pada Kantor Pelayanan Perbendaharaan Negara (KPPN) Khusus Jakarta VI - Triana Meinarsih; Binsar H. Simanjuntak (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
This study analyzes the problem of the level of user satisfaction the Office of State Treasury Service (KPPN), the factors that lead to customer dissatisfaction of KPPN, as well as the efforts of KPPN to improve customer satisfaction. This study shows that user customer satisfaction is quite high. The indicators of satisfaction are tangibility, reliability, responsiveness, assurance, and empathy. The result of Whitney Mann test of the entire indicators is> 0.05 (5%). So the valuating of five attribute in both groups, perceived service and expected service, shows a difference satisfaction. In Cartesian Diagram, the three entered in quadrant 1, in which quadrant 1 shows the expected high service, but instead low perceived service. So there is a high gap between expected service and perceived services, which lead to dissatisfaction, and efforts of KPPN’s to improve customer satisfaction with the implementation of one-stop service, no cost and improving the competence of staff.